Frequency distribution of CIE standard general skies for Subang, Malaysia - Mohammad Shahriar, Abu Nur; Mohit, Mohammad Abdul (University of Sydney, Australia, 2006)
Standard skies are very important in analysing the daylight climate of a particular region or country. Studies of their frequency distribution can help in identifying the most recurring typologies, which can then be used by researchers in modelling daylight in building. The paper describes the process of determining the occurrence of CIE Standard general Skies of Subang, Malaysia, utilizing the daylight coefficient method and global illuminance values covered from global irradiance measurments available for the location.